Determinan Nilai Perusahaan LQ 45 dengan Ukuran Perusahaan sebagai Pemoderasi - Kenny, Cristian; Maryati, Maryati; Fibrianti, Ika; Dosinta, Nina Febriana; Yunita, Khristina; Heniwati, Elok (Jurnal Akuntansi dan Keuangan, 2024)
This study investigates the role of firm size as a moderating of profitability, leverage on firm value. This study uses Price Book Value (PBV) as a proxy for firm value in LQ45 index companies for the 2017-2021 period which has not been used by previous research. The findings of this study indicate that Return on Assets and Return on Equity as proxies for profitability have no effect on firm value. Then, company size has a significant effect on firm value, while the Debt to Asset Ratio and Debt to Equity Ratio as leverage proxies have no effect on firm value. Firm size can weaken the effect of profitability on firm value. Firm size can also moderate the relationship between leverage and firm value. The findings of this study imply that company size plays an important role in attracting investors, but if it is not accompanied by good financial performance management, it will actually lead to negative perceptions about the company's financial performance.